1989
DOI: 10.1111/j.1471-4159.1989.tb01858.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines and Ca2+ Mediate Hyperosmolal Opening of the Blood‐Brain Barrier: In Vitro Studies in Isolated Rat Cerebral Capillaries

Abstract: We recently presented evidence that the reversible opening of the blood-brain barrier (BBB) by the infusion of 1.6 M mannitol into the rat internal carotid artery is mediated by a rapid stimulation of ornithine decarboxylase (ODC) activity and putrescine synthesis in cerebral capillaries. We have now investigated this hypothesis further, using isolated rat cerebral capillaries as an in vitro model of the BBB. The ODC activity of cerebral capillary preparations was enriched up to 15-fold over that of the cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In addition, in isolated capillaries, the mannitol-induced influx of 45 Ca2 + and uptake of horseradish peroxidase or deoxyglucose were inhibited by DFMO -whereas putrescine abolished this inhibition (Koenig et al, 1989c). Interestingly, the protein kinase C activator phorbol myristate acetate supplemented the effect of mannitol and this was also DFMO sensitive (Koenig et al, 1989c).…”
Section: Blood-brain Barrier Disturbancesmentioning
confidence: 84%
“…In addition, in isolated capillaries, the mannitol-induced influx of 45 Ca2 + and uptake of horseradish peroxidase or deoxyglucose were inhibited by DFMO -whereas putrescine abolished this inhibition (Koenig et al, 1989c). Interestingly, the protein kinase C activator phorbol myristate acetate supplemented the effect of mannitol and this was also DFMO sensitive (Koenig et al, 1989c).…”
Section: Blood-brain Barrier Disturbancesmentioning
confidence: 84%
“…The effect of DFMO was reversed by the administration of exogenous putrescine. Koenig et al 125,26/ also showed that hyperosmolar mannitol injected into the carotid artery induces ODC-regulated synthesis of microvascular PA allowing BBB breakdown. These studies indicate that PA synthesis is obligatory for BBB breakdown; they also suggest that the mechanism of PA action involves a ΡΑ-mediated stimulation of calcium fluxes into microvessel endothelium, leading to an increase in free cyctosolic Ca 2+ .…”
Section: Discussionmentioning
confidence: 94%
“…This suggests that the same mechanisms may be activated across a wide bandwidth of the non-ionising portion of the electromagnetic spectrum. Further, there is evidence that reversible opening of the BBB is mediated by stimulation of ornithine decarboxylase activity (Koenig et al, 1989) which may be dependent on calcium ion transport across the cell membrane and/or intracellular free calcium concentration. Since it has been shown that ornithine decarboxylase activity (Litovitz et al, 1991), intracellular free calcium concentration (Carson et al, 1990), and calcium ion transport across the cell membrane (Walleczek and Budinger, 1992) can be altered by ELF magnetic field exposure, the modulation in permeability by the total imaging procedure over the changes produced by the static exposure alone may be initiated by the stimulation of the calcium second messenger system produced by exposure to the MRI gradients which produces an ELF magnetic field.…”
Section: Discussionmentioning
confidence: 99%